Fronteira de rumo incerto : situação das políticas fronteiriças Brasil-Venezuela e o caso do “Acordo Non-Aedificandi” entre Pacaraima e Santa Elena de Uairén - González Petot, Domingo Luis Antonio (2018)
The only populated centers of relative size as well as the only land interconnection by road between Brazil and Venezuela are between the “twin cities” of Pacaraima (Roraima State, Brazil) and Santa Elena de Uairén (Bolivar State, Venezuela). Although for the two countries up to now this frontier has not been the most dynamic compared to others in their geography, new economic, social and political realities, as well as regional integration projects, have reinvigorated their activity and potential, growth in the future. In 1859 both countries established as border limit by the divortium aquarum where the basin of the Amazon river would be recognized to Brazil (except a portion of the affluent Black river) whereas the basin of the Orinoco and Essequibo rivers, to Venezuela. A long time later, because the interest of both parts to maintaining visibility at border, they sign in 1988 the Non-aedificandi agreement (our central case of study) where activities and constructions were banned in a 30 meter strip on both sides of the border. Because of observations on the site in 2011, it was notice that this Agreement should be not respected, especially on the Brazilian side. This prompted us to carry out an updated study of him and of the border policies of both countries in general, their involvement in the local population and that of the latter in those policies, including new variables such as ecological or peoples' demands which will lead to better binational knowledge and understanding.